Atributos de solos sob sistemas de uso agropecuários na mesorregião do Oeste Potiguar - RN - Ribeiro, Ana Karenina Fernandes de Sousa (2016)
The semi-arid region is extremely diverse from the point of view of their natural resources which vary according to factors such as location, soil types, lithology and climate. However, it is perceived fragility of the region under study with regard to human action, making it more susceptible site to degradation processes. Studies evaluating soil properties in Oeste Potiguar in the Rio Grande do Norte state are scarce, but its quantification in different uses and environments in an integrated manner is necessary for understanding and subsequent adoption of appropriate practices to local conditions. This study aimed to evaluate the physical and chemical properties in different agricultural uses, detecting the most sensitive in distinguishing environments. The survey was conducted in the cities of Pau dos Ferros, San Francisco West, Mossoro, Governador Dix-Sept Rosado. The areas under study have particular characteristics as to classification of soils and agricultural uses. physical fertility and analysis analyzes were performed as particle size, plasticity limits and liquidity, plasticity index and gravimetric moisture. The results were analyzed by means of multivariate analysis as the main tool, specifically factor analysis and clustering. There was a greater contribution TOC in Gleysol (favoring the increase in P, Ca 2+ and K +), favored by organic waste and poor drainage on the basis of the clay fraction. Soils showed eutrophic character (V> 50%), influenced by lithology, except Latossolo. In Gleysol and Cambisol occurred increase in liquidity limits and plasticity, due to the increase of the clay fraction and total organic carbon, increasing the gravimetric moisture to achieve crispness, with the exception of Planosol that showed low permeability on the horizon B, where the limits of plasticity and liquidity diverged, thus, greater plasticity index. In particle size analysis profiles showed changes in textural classes, especially the Gleysol with the highest silt fraction, and an indication of young soils with little weathering activity. We conclude that the physical attributes moisture, liquid limit, plastic limit, plasticity index clay, fine sand were the most sensitive in the environments distinction and pH chemicals, (H + Al), V, PST. The Planosol showed low permeability in the B horizon, thus having the greatest plasticity index distancing the limits between them. The areas studied showed acidity to alkalinity reactions with the presence of Al 3+ and (H + Al) and high salinity. The source material favored the increase in calcium, sodium, magnesium and potassium